Emergent Properties Delineate Marine Ecosystem Perturbation and Recovery. (November 2015) - Link, Jason S.; Pranovi, Fabio; Libralato, Simone; Coll, Marta; Christensen, Villy; Solidoro, Cosimo; Fulton, Elizabeth A.
Abstract : Whether there are common and emergent patterns from marine ecosystems remains an important question because marine ecosystems provide billions of dollars of ecosystem services to the global community, but face many perturbations with significant consequences. Here, we develop cumulative trophic patterns for marine ecosystems, featuring sigmoidal cumulative biomass (cumB)–trophic level (TL) and 'hockey-stick' production (cumP)–cumB curves. The patterns have a trophodynamic theoretical basis and capitalize on emergent, fundamental, and invariant features of marine ecosystems. These patterns have strong global support, being observed in over 120 marine ecosystems. Parameters from these curves elucidate the direction and magnitude of marine ecosystem perturbation or recovery; if biomass and productivity can be monitored effectively over time, such relations may prove to be broadly useful. Curve parameters are proposed as possible ecosystem thresholds, perhaps to better manage the marine ecosystems of the world. Trends: Despite ongoing debate, we assert that there are consistent, fundamental features of marine ecosystems. Key fundamental features are emergent properties of marine ecosystems that include sigmoidal cumulative biomass–trophic-level and 'hockey-stick' cumulative production–biomass curves. These consistent, theoretically supported patterns occur in over 120 marine ecosystems. A developing cumulative trophic theory builds upon past advances, widespread empirical support, and confirmation of simple predictions with observed responses. Cumulative curve parameters can help delineate when marine ecosystems are perturbed or recovered, integrating across a range of stressors and response mechanisms.